Risk Management Software – Standpoints of Users - Dražena Gašpar; Mirela Mabić; Ivica Ćorić (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The paper presents results of research related to the standpoints of users about the main attributes that risk management software should have. This research was based on a survey of appropriate number of companies in Croatia and Bosnia and Herzegovina. The authors developed the questionnaire in order to investigate the standpoints of risk managers, quality managers and others in charge of risk management, about functionality they expect risk management software should support. Namely, in today's global environment, managers and risk managers across all lines of business are accountable for a sustainable risk framework. Adequate software support enables them to take an innovative, risk-based approach to governance and compliance, to gain a holistic, enterprisewide view of risk exposure and near-real-time risk management and monitoring.Software support for risk management process should enable organisations with efficient risk evaluation and assessment, continuous monitoring, reporting and easier improvement of the process. Results of research show the main attributes that risk management software should have in order to fulfill user expectations. Finally, the paper provides some important guidelines and suggestions for risk management software development and improvement.
Keywords: O39; 330; risk management; software; survey study